Bis-phosphonated carbon nanotubes: One pot synthesis and their application as efficient adsorbent of mercury. Issue 5 (4th May 2018) - Żelechowska, Kamila; Sobota, Diana; Cieślik, Bartłomiej; Prześniak-Welenc, Marta; Łapiński, Marcin; Biernat, Jan F.
ABSTRACT: Effective, one-pot method of CNTs phosphonylation is presented. Cheap and readily available reagents are used, so the process can be easily transferred to large-scale production. The product was analyzed using spectroscopic methods (FTIR, UV-vis, XPS). Thermal properties of the bis-phosphonated nanotubes are reported for the first time. Newly obtained material was tested as an adsorbent for mercury removal from water. The sorption capacity for newly developed adsorbent was as high as 223.7 mg/g. The adsorption kinetics were studied within framework of Lagergren model, and Langmuir and Freundlich isotherms have been described. The effect of pH on the adsorption process has been evaluated and the optimal environmental conditions were determined to be neutral. The presence of bivalent ions Cd 2+, Ni 2+ in the solution did not affect adsorption efficiency of novel materials.